Clinical Manifestation, Dermoscopy, and Scanning Electron Microscopy in Two Cases of Contagious Ecthyma (Orf Nodule). (29th October 2018) - Rezende, Ana Laura Rosifini Alves; Bernardes Filho, Fred; de Paula, Natália Aparecida; Towersey, Loan; Hay, Roderick; Frade, Marco Andrey Cipriani
Abstract : Orf is a highly contagious skin disease commonly seen in goats and sheep that can be transmitted to people who have direct contact with infected animals. Here, we report the clinical manifestation, dermoscopy, and scanning electron microscopy in two women who developed skin lesions on their hands after handling goats with wounds in the udders. Human orf is usually self-limiting and no specific treatment is needed.